Family Empowerment Through the Muhammadiyah Learning Program: A Case Study at the Private University in Jakarta - Hamid, Almisar; Suradika, Suradika; Masyitoh, Masyitoh (Technium Social Sciences Journal, 2021)
The purpose of this evaluative research is to assess the implementation of the Muhammadiyah learning program which is a compulsory subject in all Muhammadiyah and Aisyiah Universities (PTMA). The study was conducted at the University of Muhammadiyah Prof. Dr. Hamka (Uhamka) from January to April 2020. This research is qualitative. The informants were selected using a purposive technique, consisting of students, lecturers, Uhamka leaders, and the leadership of the Muhammadiyah Higher Education and Research Council. Data was collected using interview techniques, Focused Group Discussion (FGD), and documentation. The data were analyzed by evaluating the CIPP model. The results of the study show that there are still several obstacles in the learning of Muhammadiyah, among others, in terms of context, there are still debates about the content of the curriculum. Renewal efforts have been made with the publication of new textbooks. There were obstacles regarding the availability, qualifications, and certification of Kemuhammadiyahan lecturers from the input side. In terms of process, the duration of learning which is only 2 credits is felt to be insufficient to implement learning with empowerment strategies. Finally, in terms of products, despite the development of student views about Muhammadiyah, these developments have not significantly changed the religious traditions they believe in so far.